Intensification of dual-phase operations using low-frequency high-power ultrasound irradiation / Seyed Ali Asgharzadehahmadi - Seyed Ali, Asgharzadehahmadi (2017)
Sonochemical reactors operate based on the release of high amount of energy from ultrasonic irradiations. Many applications in chemical processes are being developed using these reactors. However, the potential of their applications are still limited largely due to the lack of understanding about their design, operational and performance characteristics. More information about the effects of ultrasound irradiation on systems with different phases is also required in order to apply sonochemical reactors as a practical alternative for conventional stirred vessels. Accordingly, the aim in the present research is to study the effects of ultrasound irradiation on different dual-phase operations and intensify them using sonochemical reactors. The effect of ultrasonication on a gas-liquid system was investigated first by determining the gas-liquid mass transfer of oxygen dissolution in water. The influence of ultrasound power, liquid rheological properties, gas flow rate, size of tank and position of ultrasonic horn on gas-liquid mass transfer in a sonochemical reactor was studied in separate sets of experiments. Computational analysis using 3D CFD simulation was carried out in order to compare the performance of sonoreactor with conventional stirred vessel and also to visualize the behaviour of ultrasound waves within the system, fluid flow pattern and velocity, turbulence and acoustic pressure layers within the liquid. The performance of sonochemical reactors in terms of reaction yield was then investigated in a liquid-liquid system for transesterification of Jatropha curcas oil to biodiesel. The effects of ultrasound power, catalyst concentration, methanol to oil molar ratio, reaction temperature and reaction time on biodiesel yield and conversion rate were analyzed. Subsequently, the effects of ultrasound irradiation in a solid-liquid operation were also studied by determining the biodiesel yield and conversion rate of in situ transesterification process. Besides, the individual and interactive effects of other operating parameters on in situ transesterification of J. curcas seeds were investigated. Moreover, a separate set of experiments was also designed to compare the ultrasound-assisted transesterification and in situ transesterification with traditional method under mechanical stirring. Central Composite Design (CCD) was employed to design all of the experiments, develop regression models, optimize and evaluate different operating parameters. Ultrasound power, size of tank and position of ultrasonic horn were found to significantly affect the gas-liquid mass transfer in the sonochemical reactor. In the CFD simulation part, the results were illustrated as a function of acoustic streaming, fluid flow pattern, gas-liquid volume fraction and turbulence in the gas-liquid system and it was found that additional turbulence created by ultrasound played the most important role on intensifying the mass transfer phenomena compared to that in stirred vessel. In transesterification of J. curcas oil for biodiesel production in liquid-liquid system, the maximum biodiesel yield of 94.23 % and conversion rate of 98.54 % were obtained under ultrasound irradiation. In the in situ transesterification experiments in solid-liquid system, methanol to seed ratio and ultrasonic power were found to exert more significant effects on the product yield compared to the other operating parameters while catalyst concentration was the most significant parameter on the conversion rate. The highest biodiesel yield of 93.45% and conversion rate of 99.26% were also achieved in solid-liquid system. In conclusion, this study proved that sonochemical reactors could be applied as a suitable alternative for conventional stirred vessels regarding to the significant process intensification obtained under ultrasound irradiations. The obtained results in this research are helpful for understanding the effective role of ultrasound as an energy source on intensifying different dual-phase operations.